Baudelaire's ironic lighthouse: Poem as image, poem into image - Yee, J (University of California Press, 2022)
Visual interpretation can offer a means of critical exegesis, as demonstrated in this article which proposes a reading of Baudelaire’s poem ‘L’Irrémédiable’ via a series of original drawings, in a process of reverse ekphrasis. ‘L’Irrémédiable’ is read as both an ekphrastic, anti-modern poem exploring a series of old-fashioned emblems, and a radical step towards iconicity in which the shape of the poem gives spatial expression to the ironic beacon of self-awareness.